Relationship between microstructure and mechanical property of nickel-aluminum bronze alloy solidified at different cooling rate and heat treated - Razali, Nurhaulia (2014)
Nickel–Aluminium Bronze (NAB) is copper-based alloy, which widely used in marine applications because it provides high mechanical strength and low corrosion rates under turbulent flow conditions. Belongs to group of aluminium bronzes it contains 5–12 wt. % aluminium with additions of iron and nickel up to 6 wt. %. Presence of aluminium increases the mechanical properties of the alloy by the establishment of a face-centered cubic (FCC) phase that could improve the casting and hot working properties of the alloy. With the use of computer aided cooling curve thermal analysis (CA-CCTA) the phase transformation during casting can be revealed which can be done by the first derivation from the cooling curve data of the NAB alloy. This method is can be useful for designing the casting parameter of the NAB alloy in order to improve its mechanical property and obtained desired mechanical properties. In this research, the effect of cooling rate during solidification is demonstrated by using different mould during casting of NAB alloy whereby high cooling rate will produces finer grain as compare to slow cooling. Similarly, at higher cooling rate will result in higher hardness in comparison with the slower cooling rate. The mechanical properties of the as cast alloy will be further improved by applying heat treatment at temperature of 900 oC for two hours and water quenched followed by ageing at temperature of 350 oC - 400 oC for 1-3 hours and air cooled. Aged samples from ceramic mould attained highest hardness after aged at 350 oC for 3 hours and samples from permanent mould gave higher hardness after aged at 350 oC for one hours. Prolonged soaking time and increasing ageing temperature resulted in reducing hardness due to over aged.